Spectrum of Clinical Presentations and Outcomes in Children with Poisoning at a Tertiary Care Center - Zarmast Khan, Muhammad Hanif, Sadia Yasmeen, Naseem Begum, Ibrahim, Saba Afzal Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research was to better understand the severity and treatment options for paediatric poisonings at a major medical centre. Study Design: Retrospective Study Place and Duration: Niazi Medical and Dental College, Sargodha, From September, 2021 to February, 2022. Methods: There were 65 children had age 6 months to 14 years were presented in this study. All the included patients had accidental poisoning. After obtaining written consent from the parents of participants, detailed demographic information including age, sex, place of residence, and weight, was determined. Symptoms of poisoning, causes and products containing poison substances were assessed. SPSS 24.0 was used to analyze all data. Results: We found that 38 (58.5%) cases were males and females were 27 (41.5%). Most of the children 32 (49.2%) had age 6-months to 3 years, 20 (30.8%) had age 4-6 years and 13 (20%) had age 7-14 years. Diarrhea was the most common symptom found in 28 (43.1%) cases, followed by drowsiness and fever. Organo-phosphorus compounds was the most common poison substance found in 26 (40%) cases, kerosene oil in 15 (23.1%) cases, pharmaceutical drugs in 14 (21.5 %) cases, opioid poisoning in 7 (10.8%) cases and plant/atropine in 3 (4.6%) cases. Most common container of substance was bottle pack found in 22 (33.8%) cases, followed by spray bottle in 16 (24.6%) cases, glass in 11 (16.9%) cases and 21 (32.35) were others. Conclusion: In this study, we found that young male children are more susceptible to poisoning. The most frequent symptoms of poisoning from organophosphorus chemicals are diarrhea. Keywords: Accidental Poisoning, Children, Organo-phosphorous, Diarrhea